Association between early enteral nutrition and 28-Day mortality in mechanically ventilated patients with sepsis: a retrospective analysis of the MIMIC-IV database - Fuchao Xu; Geng Lu; Hao Sun; Jun Wang (BMC Infectious Diseases)
Abstract Background The optimal timing of enteral nutrition for critically ill septic patients in the intensive care unit (ICU) who require invasive mechanical ventilation has not been determined, and the influence of early enteral nutrition on clinical outcomes is unclear. Methods This retrospective observational study utilized data from the Medical Information Mart for Intensive Care IV 2.2 (MIMIC-IV 2.2) database to investigate patients with sepsis who needed invasive mechanical ventilation post-ICU admission. Patients who had enteral nutrition (EN) initiated within 72 h of ICU were categorized into the early enteral nutrition (EEN) group, while those who began enteral nutrition after 72 h were placed in the delayed enteral nutrition (DEN) group. Propensity score matching analysis was performed to compare outcomes between these two groups, with the primary outcome being 28-day mortality. Results The final analysis included 2293 patients, 1546 (67.4%) of whom received enteral nutrition within 72 h of invasive mechanical ventilation. The overall 28-day mortality rate was 31.0%. After propensity score matching employing the proximity matching method, Cox survival analysis revealed that early enteral nutrition was associated with increased 28-day mortality in septic patients on invasive mechanical ventilation (hazard ratio(HR) 1.440, 95% CI 1.179–1.760; p < 0.001). The sensitivity and robustness of the evaluation results under different models, including optimal matching (adjusted odds ratio (aOR) 1.52, 95% CI 1.21–1.92, p < 0.001), inverse probability of treatment weighting (aOR 1.27, 95% CI 1.02–1.58, p = 0.034), and logistic regression analysis (aOR 1.48, 95% CI 1.18–1.84, p = 0.001), confirmed the association between early enteral nutrition and increased 28-day mortality in mechanically ventilated septic patients. Conclusions Compared to delayed enteral nutrition, early enteral nutrition is associated with higher 28-day mortality in septic patients on invasive mechanical ventilation. Randomized controlled trials are warranted to validate these findings.